Assessment of the Carbon Footprint and VOCs Emissions Caused by the Manufacturing Process of the Footwear Industry in Bangladesh - Yead Mahmud; Md. Rashed-Ul-Islam; Md. Obaidul Islam; Tanvir Siddike Moin; Khandaker Tanzim Rahman (Textile & Leather Review, 2021)
Every industry has an impact on the environment, either good or bad, and leather and footwear industries are no exception. For the footwear industry, the main environmental impacts are the releasing of volatile organic compounds (VOCs) and solid wastes. The pressure of reducing harm to the environment is coming from both the consumers and the legislation. CO2 and VOCs are hazardous to human health and also trigger serious environment problems, such as ozone layer depletion, offensive odour, photochemical smog, acid rain and many others. Adhesives, finishing products and cleaners contribute to VOCs emissions in the footwear manufacturing industry. VOCs emission may also arise from primers, separating agents, printing inks or finishing pastes. Some most commonly produced VOCs in the footwear manufacturing industry are benzene, toluene, styrene, ethylene, xylene, acetaldehyde, formaldehyde, methyl ethyl ketone, chlorobenzene, phenol etc. All of these cause severe health problems in humans and have an adverse effect on the environment. An increasing number of footwear factories adversely affects the environment and human health. One of the largest environmental impacts of shoe industry comes from the manufacturing stages of the shoe’s life cycle. This study was carried out to measure the carbon footprint and VOCs emissions among ten selected footwear factories. The results revealed that the total energy footprint for one pair of shoes is 18.004826 MJ, the water footprint is 8.37167 litres and the carbon footprint is 9.174979 kg CO2 eq. The highest impact in terms of the carbon footprint lies in the shoe manufacturing process with a 5.85109 eq. CO2 (kg). The total VOCs consumption for a fashion shoe is around 36.5 g/pair on average. There should be an initiative taken with the aim of adjusting the choice of methods, materials, machines and the monitoring systems as well as the safety policy for the workers and the environment.